2004
DOI: 10.1190/1.1707054
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of effective porosity using geostatistics and multiattribute transforms: A case study

Abstract: The middle Eocene Kalol Formation in the north Cambay Basin of India is producing hydrocarbons in commercial quantity from a series of thin clastic reservoirs. These reservoirs are sandwiched between coal and shale layers, and are discrete in nature. The Kalol Formation has been divided into eleven units (K‐I to K‐XI) from top to bottom. Multipay sands of the K‐IX unit 2–8 m thick are the main hydrocarbon producers in the study area. Apart from their discrete nature, these sands exhibit lithological variation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(30 citation statements)
references
References 35 publications
0
29
0
1
Order By: Relevance
“…Para abordar el problema de caracterización no invasiva, se han propuesto algunas técnicas de modelación, tales como el mapeo geostadístico y transformaciones multiatributo para la estimación de la porosidad (Pramanik et al, 2004). Otros enfoques incluyen el uso de algoritmos genéticos (Dorrington & Link, 2004) o redes neuronales (Helle et al, 2001;Bhatt & Helle, 2002).…”
Section: Introductionunclassified
“…Para abordar el problema de caracterización no invasiva, se han propuesto algunas técnicas de modelación, tales como el mapeo geostadístico y transformaciones multiatributo para la estimación de la porosidad (Pramanik et al, 2004). Otros enfoques incluyen el uso de algoritmos genéticos (Dorrington & Link, 2004) o redes neuronales (Helle et al, 2001;Bhatt & Helle, 2002).…”
Section: Introductionunclassified
“…Existing methods for high-dimensional interpolation include linear regression ͑Hampson et al, 2001;Russell et al, 2002;Hansen et al, 2008͒, spline interpolation, nearest neighbor, cokriging ͑Doyen, 1988͒, and neural networks ͑Hampson et al, 2001Russell et al, 2002;Pramanik et al, 2004;Herrara et al, 2006͒. Some comparative studies of these methods are available.…”
Section: Multivariate Interpolationmentioning
confidence: 99%
“…Russell et al ͑2002͒ compare generalized regression neural networks and radial basis function networks for prediction of log properties from seismic attributes. Pramanik et al ͑2004͒ compare the application of linear regression, neural networks, cokriging with impedance, and cokriging of actual porosity estimates with a porosity map obtained using a neural network. Herrara et al ͑2006͒ uses a combination of linear regression and neural networks.…”
Section: Multivariate Interpolationmentioning
confidence: 99%
“…This is done in two steps: (1) a training process in which the target logs and the seismic attribute volumes are analyzed (by applying a least-squares approach) at both wells to derive a statistical function relating the target logs to the attribute volumes and (2) applying the derived function to create corresponding target log values for each trace in the seismic volume. Several authors have shown the benefits of geostatistical multiattribute transforms to predict porosity and lithology in the seismic volume (Hampson et al, 2001;Pramanik et al, 2004;Calderon and Castagna, 2005).…”
Section: Multiattribute Regression Analysismentioning
confidence: 99%